The Organic Fertilizer Application Effect on Yield and Quality of Two Introduced Rice Varieties in Timor Leste - Marcus dos Santos Soares; Tri Handoyo; Kacung Hariyono (Jurnal Agrinika: Jurnal Agroteknologi dan Agribisnis, 2023)
The Lahoten Musan Kabuar and Lahoten Musan Lotuk Naruk varieties are two introduced rice varieties from Timor Leste. Optimization of cultivation techniques using organic fertilizers with different doses is carried out to obtain the best growth and yield quality. The research was carried out from December 2021 to April 2022 using the CDAST laboratory greenhouse at the Universitas Jember. The experimental design used a completely randomized design (CRD) with two factors. The main factor is the type of rice varieties which consists of 2 levels, namely the Lahoten Musan Kabuar variety (V1) and the Lahoten Musan Lotuk Naruk variety (V2). The second factor is the dose of organic fertilizer application, which consists of 4 levels, namely 0 tons ha-1 (P0), 2 tons ha-1 (P1), 4 tons ha-1 (P2), and 6 tons ha-1 (P3). The results showed an interaction between the use of organic fertilizer and the type of varieties on plant height, chlorophyll content, protein content, fat content, and amylose content. Whereas the application of organic fertilizer had no significant effect on the parameters of the number of tillers, number of panicles per plant, number of seeds per panicle, the weight of 100 seeds, carbohydrate content, and water content. The results of DMRT on interaction parameters show that the organic fertilizer dose factor has a more dominant influence than the variety factor.